Maize Under Pressure: Spread of Helicoverpa armigera into Romanian Agroecosystems - Emil Georgescu; Maria Toader; Ioan Sebastian Brumă; Lidia Cană; Luxița Rîșnoveanu; Paula-Lucelia Pintilie; Roxana-Georgiana Amarghioalei; Alina Crețu; Cristina Cionga; Cristina Radu; Horhocea Daniela (Agronomy, 2025)
This paper presents a five-year study monitoring cotton bollworm (Helicoverpa armigera) flight dynamics using pheromonal traps and a study relating to the behavior of nine maize hybrids from two maturity groups in response to a pest attack in 2024. The monitoring and field assessments were conducted in Southeast Romania, Călărași County, at the NARDI Fundulea. During the monitoring period, from 2020 to 2024, air temperature was higher than average in the summer months while rainfall was below average, except in June 2021. The total number of moths captured in the traps was 246 in 2020, 406 in 2021, 5064 in 2022, 1024 in 2023, and 4145 in 2024. In the middle of July 2022, the average captured moths per trap was 483.3; in the middle of September, it was 589.0 catches. In 2024, in the last 10 days of July, the average captured moths per trap was 311.7; in the last 10 days of August, it was 358.0, while in the middle of September, it was 362.3. In 2024, at the beginning of August, the attack incidence of corn earworm on maize hybrids ranged from 43.75 to 53.75%, and on 13 September, it was 100% for all hybrids. This is the first report from southeast Romania that mentions a higher population of cotton bollworm in the late summer and beginning of autumn and the first report to mention a large number of pest attacks on maize cobs in September.